Metabolomic Profiling of the Desiccation-Tolerant Medicinal Shrub Myrothamnus flabellifolia Indicates Phenolic Variability Across Its Natural Habitat: Implications for Tea and Cosmetics Production - Bentley, Joanne (Molecules, 2019)
The leaves and twigs of the desiccation-tolerant medicinal shrub Myrothamnus flabellifolia are harvested for use in traditional and commercial teas and cosmetics due to their phenolic properties. The antioxidant and pharmacological value of this plant has been widely confirmed; however, previous studies typically based their findings on material collected from a single region. The existence of phenolic variability between plants from different geographical regions experiencing different rainfall regimes has thus not been sufficiently evaluated. Furthermore, the anthocyanins present in this plant have not been assessed. The present study thus used an untargeted liquid chromatography-tandem-mass spectrometry approach to profile phenolics in M. flabellifolia material collected from three climatically distinct (high, moderate, and low rainfall) regions representing the western, southern, and eastern extent of the species range in southern Africa. Forty-one putative phenolic compounds, primarily flavonoids, were detected, nine of which are anthocyanins. Several of these compounds are previously unknown from M. flabellifolia. Using multivariate statistics, samples from different regions could be distinguished by their phenolic profiles, supporting the existence of regional phenolic variability. This study indicates that significant phenolic variability exists across the range of M. flabellifolia, which should inform both commercial and traditional cultivation and harvesting strategies.